“I really wanted to be able to contribute something”: understanding student motivations to create meaningful global health experiences - Hetherington, Erin; Hatfield, Jennifer (Revue canadienne de l’éducation médicale, 2012)
Background: Global health is an area of increasing interest among health professionals, students and educators. This study aims to explore students’ motivations and experiences with an undergraduate global health research program in low and middle-income countries and to assess student learning and areas for program improvement. Methods: All students participating in the Global Health Research Program at the University of Calgary in the summer of 2009 were asked to participate in the study (n=11). In-depth interviews were conducted with students prior to departure and upon their return. Discourse analysis was used to identify interpretive repertoires and to determine how the use of repertoires improves our understanding of students’ experiences. Results: Prior to departure, students were highly motivated to "give back" to host communities. Upon return, students felt that their experience had been more about "building relationships" with others than individual contributions to hosts. Discussion: Students' altruistic motivations dominated the discourse, and most students incorporated core concepts from a preparation course only after their international experience. Extensive preparation, supervision and follow-up support can mitigate many of the risks of short-term global health experiences while providing a safe opportunity for significant learning.